The Relationship between Teachers' Occupational Professionalism and Burnout - Kürşad Yılmaz; Mustafa Çelik (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
In this study, it was aimed to determine the relationship between teachers’ occupational professionalism and burnout. The study was designed in the survey model. The sample of the study is consisted of 358 teachers in the city center of Kütahya. The study data was collected The Occupational Professionalism Scale of Teachers and The Maslach Burnout Inventory. In the study, descriptive statistics, t-test for comparisons and one way variance analysis, and Pearson Product Moment Correlation Coefficient Correlation Coefficient were used. According to the findings obtained in the study; teachers have a moderate level of perception of professionalism. Teachers participated in the study showed the highest level of participation among the sub-dimensions of occupational professionalism as Professional Awareness, Emotional Labor, Contribution to Organization, and Personal Development dimensions respectively. While teachers’ views related to their occupational professionalism show statistically significant differences in some dimensions according to the gender, branch, seniority and total number of students in the school variables; do not show statistically significant differences according to the age, marital status, school type, educational status and total number of teachers in the school variables. Teachers participated in the study have a low level of burnout. Teachers showed the highest level of participation among the sub-dimensions of burnout as Personal Accomplishment, Emotional Exhaustion, and Depersonalization dimensions respectively. While teachers’ views related to their burnout show statistically significant differences in Personal Accomplishment dimension according to the age, school type, and seniority variables; do not show statistically significant differences according to the gender, marital status, branch, educational status, total number of students in the school and total number of teachers in the school variables. While there are low level, in the opposite direction and significant relationships between the teachers’ total points of occupational professionalism and teachers’ views related to Emotional Exhaustion and Depersonalization, there are mid-level, in the same direction and significant relationships between the teachers’ total points of occupational professionalism and teachers’ views related to Personal Accomplishment.